Efficient in vitro multiplication of Aechmea Little Harv and Tillandsia cyanea linden Ex K. Koch - Cueva Agila, A. (2017)
In vitro plant regeneration of Aechmea 'Little Harv' and Tillandsia cyanea, (Bromeliaceae), two endangered and important ornamental bromeliads native to Ecuador was achieved from seedling explants. T. cyanea seedlings germinated or underwent indirect shoot organogenesis from callus when cultivated in a Murashige and Skoog (1962) nutrient medium in the presence of various levels of NAA (0.5 or 1.0 mg I -1) in combination with BAP (0.1, 0.5 or 1.0 mg I -1), plus 40 mg I -1 adenine. A. 'Little Harv' seed expiants formed adventitious shoots without callus initiation. In both plants, the best shoot regeneration (approx. 9-10 shoots/expiant) was obtained using 1.0 mg I -1 NAA and 0.1 mg I -1 BAP, in combination with adenine, but other growth regulator combinations were also successful. In the case of Aechmea, the addition of IAA instead of NAA was less efficient (2 shoots/expiant). In addition to shoot formation 1 mg I -1 NAA and 0.1 mg I -1 induced callus on approx. 30% of T. cyanea and 8% of A. 'Little Harv' expiants. Isolated shoots formed roots after subculture in growth regulator-free media.